Luteolin Alleviates Cadmium-Induced Kidney Injury by Inhibiting Oxidative DNA Damage and Repairing Autophagic Flux Blockade in Chickens - Kanglei Zhang; Jiahui Li; Wenxuan Dong; Qing Huang; Xueru Wang; Kai Deng; Waseem Ali; Ruilong Song; Hui Zou; Di Ran; Gang Liu; Zongping Liu (MDPI AG, 2024)
Chickens are a major source of meat and eggs in human food and have significant economic value. Cadmium (Cd) is a common environmental pollutant that can contaminate feed and drinking water, leading to kidney injury in livestock and poultry, primarily by inducing the generation of free radicals. It is necessary to develop potential medicines to prevent and treat Cd-induced nephrotoxicity in poultry. Luteolin (Lut) is a natural flavonoid compound mainly extracted from peanut shells and has a variety of biological functions to defend against oxidative damage. In this study, we aimed to demonstrate whether Lut can alleviate kidney injury under Cd exposure and elucidate the underlying molecular mechanisms. Renal histopathology and cell morphology were observed. The indicators of renal function, oxidative stress, DNA damage and repair, NAD+ content, SIRT1 activity, and autophagy were analyzed. In vitro data showed that Cd exposure increased ROS levels and induced oxidative DNA damage and repair, as indicated by increased 8-OHdG content, increased γ-H2AX protein expression, and the over-activation of the DNA repair enzyme PARP-1. Cd exposure decreased NAD+ content and SIRT1 activity and increased LC3 II, ATG5, and particularly p62 protein expression. In addition, Cd-induced oxidative DNA damage resulted in PARP-1 over-activation, reduced SIRT1 activity, and autophagic flux blockade, as evidenced by reactive oxygen species scavenger NAC application. The inhibition of PARP-1 activation with the pharmacological inhibitor PJ34 restored NAD+ content and SIRT1 activity. The activation of SIRT1 with the pharmacological activator RSV reversed Cd-induced autophagic flux blockade and cell injury. In vivo data demonstrated that Cd treatment caused the microstructural disruption of renal tissues, reduced creatinine, and urea nitrogen clearance, raised MDA content, and decreased the activities or contents of antioxidants (GSH, T-SOD, CAT, and T-AOC). Cd treatment caused oxidative DNA damage and PARP-1 activation, decreased NAD+ content, decreased SIRT1 activity, and impaired autophagic flux. Notably, the dietary Lut supplement observably alleviated these alterations in chicken kidney tissues induced by Cd. In conclusion, the dietary Lut supplement alleviated Cd-induced chicken kidney injury through its potent antioxidant properties by relieving the oxidative DNA damage-activated PARP-1-mediated reduction in SIRT1 activity and repairing autophagic flux blockade.